Herpes Simplex Virus Type 2 Myelitis: Case Report and Review of the Literature - Raffaele Nardone; Raffaele Nardone; Viviana Versace; Francesco Brigo; Frediano Tezzon; Giulio Zuccoli; Slaven Pikija; Larissa Hauer; Johann Sellner; Johann Sellner (Frontiers in Neurology, 2017)
Non-traumatic myelopathies can result from a wide spectrum of conditions including inflammatory, ischemic, and metabolic disorders. Here, we describe the case of a 60-year old immunocompetent woman who developed acute back pain followed by rapidly ascending flaccid tetraparesis, a C6 sensory level, and sphincter dysfunction within 8 h. Acyclovir and steroids were started on day 2 and herpes simplex virus type 2 (HSV-2) was confirmed by polymerase chain reaction in cerebrospinal fluid. Magnetic resonance imaging revealed a bilateral anterior horn tractopathy expanding from C2 to T2 and cervicothoracic cord swelling. Screening for paraneoplastic antibodies and cancer was negative. Neurophysiology aided in the work-up by corroborating root involvement. Recovery was poor despite early initiation of antiviral treatment, adjuvant anti-inflammatory therapy, and neurorehabilitation efforts. The clinical course, bilateral affection of the anterior horns, and early focal atrophy on follow-up magnetic resonance imaging take a necrotizing myelitis potentially caused by intraneuronal spread of the virus into consideration. Further, we summarize the literature on classical and rare presentations of HSV-2 myeloradiculitis in non-immunocompromised patients and raise awareness for the limited treatment options for a condition with frequent devastating outcome.